Diagnostic value of the enzyme-linked immunosorbent assay for detection of Candida albicans cytoplasmic antigen in sera of cancer patients. - Araj, G F (1982)
To diagnose systemic candidiasis we developed an enzyme-linked immunosorbent assay (ELISA) for the quantitation of Candida albicans cytoplasmic antigen in sera of cancer patients. The antigen concentration was evaluated in 59 patients divided into several groups according to clinical, histological, and microbiological findings as well as antimicrobial treatment. All of seven patients with proven disseminated candidiasis had elevated antigen concentrations (mean = 1,200 ng/ml). Among 13 patients with suspected disseminated candidiasis, 9 had elevated antigen concentrations (mean = 1,039 ng/ml). The remaining four patients showed negative antigen (less than 125 ng/ml). In a group of patients with fever of unknown origin, 5 of 17 had high antigen concentrations (mean = 1,220 ng/ml) and the rest were negative. Patients with bacterial infection (6 patients), aspergillosis (3), cryptococcosis (4), coccidioidomycosis (3), and no infection (6), as well as normal healthy adults (31), had antigen concentrations of less than 100 ng/ml. This ELISA is rapid, sensitive, and specific and is a helpful diagnostic tool in the evaluation of candidiasis in cancer patients.